Intraocular Pressure, Tear Production, and Ocular Echobiometry in Guinea Pigs (Cavia porcellus) - Rajaei, Seyed Mehdi (J Am Assoc Lab Anim Sci, 2016)
The purpose of this study was to evaluate intraocular pressure (IOP) by means of rebound tonometry, to assess tear production by using the endodontic absorbent paper point tear test (EAPTT) and phenol red thread test (PRTT), and to determine the effects of time of day on IOP and tear production in guinea pigs. The study population comprised 24 healthy adult guinea pigs (12 male, 12 female; 48 eyes) of different breeds and ranging in age from 12 to 15 mo. IOP and tear production were measured at 3 time points (0700, 1500, and 2300) during a 24-h period. Overall values (mean ± 1 SD) were: IOP, 6.81 ± 1.41 mm Hg (range, 4.83 to 8.50); PRTT, 14.33 ± 1.35 mm (range, 12.50 to 16.83); and EAPTT, 8.54 ± 1.08 mm (range, 7.17 to 10.0 mm). In addition, ultrasound biometry was performed by using a B-mode system with linear 8-MHz transducer. This study reports reference values for IOP and tear production in guinea pigs.